Male-Biased Partial Migration in a Giraffe Population - Brown, Michael B.; Bolger, Douglas T. (Frontiers in Ecology and Evolution, 2020)
Partial migration is a common movement phenomenon in ungulates, wherein part of the population remains resident while another portion of the population transitions to spatially or ecologically distinct seasonal ranges. Although widely documented, the causes of variation in movement strategies and their potential demographic consequences are not well understood. Here, we used GPS telemetry data and individual-based photographic surveys to describe evidence for the partial migration of giraffe (Giraffa camelopardalis) in the tropical savanna habitat of Murchison Falls National Park, Uganda. Seasonal movements in giraffe have been described but have not been systematically investigated within the framework of partial migration. We characterized movement behaviors of eight female GPS tracked giraffe across one full year using a model-driven approach of net-squared displacement metrics. To further evaluate these space use patterns at the population-level, we used closed robust design multi-state capture recapture models derived from individually based photographic surveys collected seasonally over three years. We also characterized environmental conditions associated with seasonal space use by conducting ground-based vegetation surveys and analyzing remotely sensed phenology data. Our results from both individually based telemetry models and population-level multi-state models suggest intra-population variation in seasonal space use strategies with three dominant movement classes: 1) Residents in deciduous savanna characterized by Acacia sieberiana, Acacia senegal, Harrisonia abyssinica and Crateva adansonii in the far western end of the park. 2) Residents in the broadleaf savannas characterized by Pseudocedrela kotschyi, Stereospermum kunthianum, Termalia spp. and Combretum spp.in the central sector of the park 3) Male-biased migrants that transitioned seasonally between the acacia savanna in the wet seasons and the broadleaf savanna in the dry seasons. Our results offer insights into how giraffe navigate spatiotemporally dynamic environments at both individual and population levels, providing ecological mechanisms for the emergent population dynamics of these large-bodied topical browsers.